院内感染予防と口腔ケアの重要性 - 渋谷, 恭之 (日本口腔外科学会雑誌, 2010)
The current foundation of preventing nosocomial infection in dental settings are “Guidelines for infection control in dental health-care settings” announced in 2003 by Centers for Disease Control and Prevention (CDC). These guidelines employ a concept of standard precaution in clinical dentistry, and had a great influence on “Guideline for infection control in dental prosthetics” established in 2007 by Japan Prosthodontic Society and “Guideline for infection control in dentistry” announced by the dental division of the infection control conference of the national university hospitals in 2008. On the other hand, there have been many reports about oral care, for instance, ‘1) oral care prevents aspiration-related pneumonia', ‘2) oral care decreases the onset rate of the influenza to a one-tenth, (oral care decreases significantly neuraminidase and protease which bacteria produce) ', ‘3) oral care reduces a side effect in the oral cavity by the chemoradiotherapy', ‘4) oral care prevents ventilator-associated pneumonia in ICU', ‘5) oral care is useful for symptom relief in terminal illness', and an importance of oral care has been widely noticed in late years.